Rotor angle deviation regulator to enhance the rotor angle stability of synchronous generators - Murad, Nor Syaza Farhana Mohamad; Kamarudin, Muhammad Nizam; Zakaria, Muhammad Iqbal (Institute of Advanced Engineering and Science, 2024)
Occurrences of disturbance affect the rotor angle operation of a synchronous generator in the generation system of a power system. The disturbance will disrupt the synchronous generator's rotor oscillation and result in rotor angle instability, which will degrade the power system's performance. This paper aims to develop a Lyapunov-based rotor angle deviation regulator for the nonlinear swing equation of a synchronous generator. The proposed regulator is expected to assure asymptotic stability of the rotor angle and robustness to uncertainty. Backstepping and Lyapunov redesign techniques are employed in developing the regulator. To validate the effectiveness and robustness of the regulator, a simulation in MATLAB/Simulink is carried out. The simulation result shows that the asymptotic stability and robustness of the regulator are guaranteed regardless of the disturbance.